The effect of mulching on the growth performance of aerobic paddy / Hariz Hazwan Anuar - Anuar, Hariz Hazwan (Faculty of Plantation and Agrotechnology, 2018)
This research was conducted to investigate the effect of mulching on the growth performance of aerobic paddy at Universiti Teknologi Mara (UiTM), Jasin Campus Melaka. The objectives of this study is to investigate the effect of using different type of mulching on aerobic paddy growth and also to identify the best type of mulching on paddy growth performance. This experiment was carried out in Completely Randomized Design (CRD). There were four treatments and also five replications that had been used in this experiment. The treatment consisted of Mucuna bracteata, Gliricidia spp. ,Vigna unguiculata, and also no mulching (control) and each of the treatment consist of five replications. Each paddy plant was planted in a pot and each pot were applied with 20 g of mulching act as treatments. Aerobic paddy variety (MR1A) was choosed in this experiment because of the rapid plant growth and this experiment was conducted for 70 days. The result showed that the paddy plant that applied with mulching had better growth performance for all parameter included plant height, number of tillers and plant biomass. Gliricidia spp. was the best type of mulching among the other because it had good growth performance according to the parameter result. It had the highest mean number for plant height (103.62 cm), number of tillers (11.47) and plant biomass (181.97g). Lastly, the application of mulching on paddy plant can give many advantages because it showed that it had significantly affect the plant growth compared to non mulching application.